The Socially Responsible Investment Sukuk as a Financial Tool to Address the Risk of Climate Change - Qutaiba, Mohammad; Owais, Mohd (Talaa : Journal of Islamic Finance, 2023)
The purpose of this paper is to emphasize the likelihood of Socially Responsible Investment (SRI) Sukuk to be used as a tool to address the climate changes and improve the environment and economy by generating positive social impact. This paper has adopted a descriptive and analytical approach, as this research paper has used qualitative methodology and analyzes the commonalities between SRI Sukuk and SDGs as a financial tool to address the risk of climate change The literature review revealed a growing participation and interest in SRI Sukuk. Funds and proceeds are increasing at an increasing rate annually. Additionally, the paper considers the factors of Sustainable Development Goals (SDGs) as well as Environmental, Social, and Governance (ESG) objectives, embedding SRI Sukuk with positive impact. This paper is solely focused on the conceptual nature on SRI Sukuk and Green Sukuk. Additional research is needed to better understand different segments of social impact. Despite gaining international attention from many countries, SRI Sukuk remains a topic with relatively low research and user engagement within Islamic Finance. This paper aims to raise awareness and improve comprehension of SRI Sukuk within Islamic Finance.